Penambahan inulin dan Lactobacillus acidophilus dalam pakan menggunakan sumber protein mikropartikel terhadap pertumbuhan tulang broiler - Lilik Krismiyanto; Nyoman Suthama; Bambang Sukamto; Azki Azhari Azmi (Livestock and Animal Research, 2022)
Objective: This study aimed to examine the effect of the combination of inulin from dahlia tuber extract (Dahlia variabilis) and Lactobacillus acidophilus in rations using microparticle protein sources on bacteria population, pH of intestinal, protein digestibility, calcium (Ca) retention, bone length, and weight, bone Ca mass, bone-meat ratio and body weight gain in broiler chickens.Methods: The livestock used were 216-day old chicks (DOC) Cobb strain broiler chickens with an average body weight of 42,62 ± 0,20 g. The study was arranged based on a completely randomized design (CRD) with a 3 × 3 factorial pattern with 3 replications and 8 bird each. Factor A inulin from inulin from dahlia tuber extract/IDTE 3 levels, namely A1 (0%), A2 (0,58%), and A3 (1,16%). Factor B L. acidophilus 3 levels, namely B1 (0%), B2 (0,6%), and B3 (1,2%). Parameters measured included bacteria population, pH of intestinal, protein digestibility, Ca retention, bone length, and weight, bone Ca mass, meat-bone ratio and body weight gain, but there is no interaction with femur length. The data was processed using the variance test at the 5% level and Duncan's further difference test at the 5% level.Results: The results showed that the combination of IDTE and L. acidophilus added to feed containing a protein source of microparticles showed a significant interaction (P<0,05) on bacteri population, pH of intestinal, protein digestibility, Ca retention, bone length, and weight, bone Ca mass, and meat-bone ratio. The treatment of each factor A and B had no significant effect (P>0,05) on the length of the femur.Conclusions: The addition of a combination of dahlia tuber extract inulin at the level of 1,16% and L. acidophilus as much as 1,2% of a diet using microparticle protein sources increased lactic acid bacteria population, protein digestibility, calcium retention, femur and tibia bone weight, bone meat ratio, body weight gain in broiler chickens and lower the pH of the small intestine and coliform population, but resulted in long femur bones.